2020
DOI: 10.1111/jcmm.15250
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells alleviate rat diabetic nephropathy by suppressing CD103+ DCs‐mediated CD8+ T cell responses

Abstract: Diabetic nephropathy (DN) as a kind of serious microvascular complication of Diabetes Mellitus (DM) usually causes the end‐stage of renal disease (ESRD). Studies have demonstrated that CD103+ dendritic cells (DCs) exhibited a renal pathogenic effect in murine chronic kidney disease (CKD). Mesenchymal stem cells (MSCs) can alleviate DN and suppress the DCs maturation. To explore the role of CD103+ DCs and the potential mechanisms underlying MSCs‐mediated protective effects in DN, we used bone marrow MSCs (BM‐MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…Matured DCs produce cytokines and costimulatory molecules and activate T lymphocytes and renal macrophages, thus mediating inflammation and kidney damage. Experimental immunomodulatory strategies, such as mesenchymal stem cell transplantation and Fms-like tyrosine kinase 3 inhibitor, reduce the population and maturation of DCs and ameliorate inflammation and CKD [55,56]. However, there is still limited information about the distinct functions of DCs' subsets in the pathogenesis of DN.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Matured DCs produce cytokines and costimulatory molecules and activate T lymphocytes and renal macrophages, thus mediating inflammation and kidney damage. Experimental immunomodulatory strategies, such as mesenchymal stem cell transplantation and Fms-like tyrosine kinase 3 inhibitor, reduce the population and maturation of DCs and ameliorate inflammation and CKD [55,56]. However, there is still limited information about the distinct functions of DCs' subsets in the pathogenesis of DN.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…For example, it has been shown that murine BM-MSCs induce the differentiation into regulatory DCs by HGF secretion ( Lu et al, 2019 ). Further functional data revealed that rat MSCs inhibit the maturation of CD103 + DCs, leading to a decreased ability to prime CD8 + T cells ( Zhang et al, 2020 ). Additionally, murine DCs that were treated with MSC-derived exosomes failed to stimulate T-cell proliferation upon LPS activation ( Shahir et al, 2020 ).…”
Section: Modulation Of Innate Immunity By Mscsmentioning
confidence: 99%
“…Dendritic cells (DCs) facilitate renal inflammation via promoting CD8+ T cell proliferation and activation during the development of CKD ( 124 , 125 ). Mechanistically, TGF-β1 promotes DCs accumulation in fibrotic tissue ( 126 ) and modulates DCs-mediated proliferation and activation of T cells ( 127 130 ), contributing to the imbalance between Th17 and Treg ( 131 ) and the interleukin 17 (IL-17) release from naive CD4 + cells ( 132 ).…”
Section: Tgf-β1 In Adaptive Immunity Of Ckdmentioning
confidence: 99%